2008
DOI: 10.1002/cncr.23825
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival outcomes based on histologic grading in patients with head and neck mucoepidermoid carcinoma

Abstract: BACKGROUND Histopathologic grade of mucoepidermoid carcinoma (MEC) is an established predictor of prognosis and affects treatment protocol. Tumor behavior is more aggressive in high-grade than in low-grade MEC, leading to a more intensive treatment protocol. Outcomes for patients with intermediate-grade MEC are less clear; therefore, the optimal treatment protocol for this group is not well defined. The treatment protocol and survival outcomes of patients treated for MEC of the head and neck was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
147
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(173 citation statements)
references
References 34 publications
10
147
5
2
Order By: Relevance
“…20 Perineural invasion (p=0.746) was seen in 7(35%) cases of AdCC in the current study which is in concurrence with the results of other studies 10 Table- dictates the treatment protocol for the patients of MEC. 6,11,14 The study conducted by Nance 19 Lymph node metastasis were found to be significantly associated with the grade of tumour (p=0.01) being negative in all grade I tumours and positive in 4(44.5%) and 5(55.5%) cases of intermediate and high grade MEC respectively. These results are in accordance to the study conducted by Chen 20 for the fact that highest number of nodal metastasis were seen in high grade tumours (56.8%).…”
Section: Discussionmentioning
confidence: 96%
“…20 Perineural invasion (p=0.746) was seen in 7(35%) cases of AdCC in the current study which is in concurrence with the results of other studies 10 Table- dictates the treatment protocol for the patients of MEC. 6,11,14 The study conducted by Nance 19 Lymph node metastasis were found to be significantly associated with the grade of tumour (p=0.01) being negative in all grade I tumours and positive in 4(44.5%) and 5(55.5%) cases of intermediate and high grade MEC respectively. These results are in accordance to the study conducted by Chen 20 for the fact that highest number of nodal metastasis were seen in high grade tumours (56.8%).…”
Section: Discussionmentioning
confidence: 96%
“…[4][5][6][7] Nevertheless, all tumors with histologic appearances defined as mucoepidermoid carcinoma are considered malignant. 8 Although efforts have been made to identify clinically useful biomarkers for grading and prognostication [9][10][11][12] there is yet no unifying concept on how to classify mucoepidermoid carcinomas.…”
mentioning
confidence: 99%
“…All our cases of low/intermediate grade MEC had a pattern of p27/ skp-2 expression more similar to MST from proposed intercalated duct origin. As a test, we allocated low/intermediate grade MEC to the group of MST of intercalated duct origin and discovered that the differences in skp-2 expression between the 2 histogenetic groups were highly significant: intercalated duct histogenesis (0%) and [27,28] while others prefer to classify them as high grade tumors [29]. In our survival study, 2 (18%) patients with MEC succumbed to their disease, and both were high grade tumors.…”
Section: Discussionmentioning
confidence: 96%